Pengaruh Kesehatan Kerja dan SOP Produksi ISO 9001 terhadap Kualitas Kerja Karyawan (Studi Kasus pada Perusahaan Karet) - Ardianto, Marcelinus Bily; Astono, Anjar Dwi (UNIVERSITAS KALBIS, 2025)
This study aims to determine the effect of occupational health and ISO 9001 production SOP on the quality of work of employees in a rubber company. This study uses a quantitative approach. This research was condcted with the unit analysis of Rubber Companies, with a population of 41 people. The sampling method used is Non-Probability sampling, with a saturated sample type, sampling with a total of 41 respondents, with a questionnaire data collection technique. Data processing method using multiple linear regression analysis. The results of this study concluded that there is a significant effect of occupational health on employee work quality, there is a significant effect of ISO 9001 production SOP on employee work quality, and there is a significant simultaneous influence between occupational health variables and ISO 9001 production SOP on employee work quality.